영화영어에서 개념적 메타포(Conceptual Metaphor)의 역할과 교수법 제안 - 류도형(Ryu Dohyung) (Journal of English Teaching through Movies and Media, 2020)
The purpose of this paper is to suggest a way for Movie English classes to overcome the discrepancy between the enjoyment of watching a movie and the tedium in using it for language learning. In order to do this, three notions were used in this paper: conceptual metaphor, source domain, and target domain (Lakoff & Johnson, 2001). Seven scenes from an American gothic fantasy movie, Beautiful Creatures, were used. This paper mainly used the metaphor identification procedure (MIP) (Pragglejaz Group, 2007) to identify metaphors. Following MIP, each scene was initially read to ensure the meaning of the scene was understood. Second, the EFL teacher tried to find each characters’ conceptualization of their own world in the movie. Third, the teacher would tell the conceptual metaphor corresponding to their conceptualization. Last, the teacher would point out the source and target domains and ask students to choose relevant utterances appropriate in the source domain for which students could find many expressions. The whole procedure indicates that movie utterances can be taught in a meaningful and enjoyable way to EFL students and offers a way for EFL teachers to approach movie English instruction. KCI Citation Count: 0